Molecular Basis of Bicyclic Boronate β-Lactamase Inhibitors of Ultrabroad Efficacy – Insights From Molecular Dynamics Simulation Studies - Lence, Emilio; González-Bello, Concepción (Frontiers in Microbiology, 2021)
β-lactam antibiotics represent about 70% of all antibacterial agents in clinical use. They are safe and highly effective drugs that have been used for more than 50 years, and, in general, well tolerated by most patients. However, its usefulness has been dramatically reduced with the spread and dissemination worldwide of multi-drug resistant bacteria. These pathogens elude the therapeutic action of these antibiotics by expressing β-lactamase enzymes that catalyze the hydrolysis of their β-lactam ring to give inactive products, which is one of the most relevant resistance mechanisms in deadly pathogens such as Pseudomonas aeruginosa, Acinetobacter baumannii and Enterobacteriaceae. From the drug development point of view, the design of an efficient β-lactamase inhibitor able to block this antibiotic resistance mechanism and restore β-lactam antibiotics efficacy is challenging. This is due to: (i) the huge structural diversity of these enzymes in both the amino acid sequence and architecture of the active site; (ii) the distinct hydrolytic capability against different types of substrates; (iii) the variety of enzyme mechanisms of action employed, either involving covalent catalyzed processes (serine hydrolases) or non-covalent catalysis (zinc-dependent hydrolases); and (iv) the increasing emergence and spread of bacterial pathogens capable of simultaneously producing diverse β-lactamases. Hence, a long-pursued goal has been the development of ultrabroad-spectrum inhibitors able to inhibit both serine- and metallo-β-lactamases. The recent development of taniborbactam (formerly VNRX-5133) and QPX7728, which are bicyclic boronate inhibitors currently under clinical development, represents a huge step forward in this goal. In this article, the molecular basis of the ultrabroad-spectrum of activity of these boron-based inhibitors is analyzed by Molecular Dynamics simulation studies using the available crystal structures in complex with both inhibitors, or the models constructed from wild-type forms. The efficacy of taniborbactam and QPX7728 is compared with the cyclic boronate inhibitor vaborbactam, which is the first boron-based β-lactamase inhibitor approved by the FDA in combination with meropenem for the treatment of complicated urinary tract infections.